Optimizing Tourism at the Menaming Village Dam, Rokan Hulu, Riau - Asral; Dimas Permana Lubis; Zikri Anugerah; Rosianna Purba; Ropina Emwarjati Sihombing; Romarito Gesi Caloria Manurung; Reni Febriani; Amalda Syahraemy Panggabean; Zahwa Khairani Azhar; Adillah Rahmatul Ummi; Lukluk Ul Masykuroh (Indonesian Journal of Advanced Social Works, 2023)
The Integrated Community Service Program (KKN Terintegrasi Abdimas) in Menaming Village, Riau Province, is a student-driven initiative to harness the area's tourism potential. KKN represents a multidisciplinary approach to community service, aiming to benefit the local populace. The focal point of this endeavor is Menaming Dam, a crucial element in the daily lives of the villagers. Students successfully crafted a comprehensive plan, which involved constructing water turbines for a basic power source and implementing nighttime illumination. They also ran awareness campaigns promoting environmental hygiene and positioning Menaming Dam as a tourist hotspot. Consequently, Menaming Dam's allure as a tourist destination has notably surged. Qualitative research methods, including field surveys, observations, tourism poster creation, gate construction, and social media promotion, were employed. Results show that KKN Terintegrasi Abdimas has achieved resounding success, positively impacting Menaming Village. To fully capitalize on its considerable tourism potential, the local government should extend support. Government-sponsored training and facilities are anticipated to aid the village in tourism development, fostering local economic growth. Continual optimization of tourism potential and available natural resources is vital for a more advanced and modern future.